Pemikiran Komputasi (Computational Thinking) dalam Pemecahan Masalah - Miksan Ansori (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2020)
Computational thinking is a very necessary capability in the face of the rapid development of ICT and complex. Besides, the 4.0 industrial era also requires computerization in all areas. Nevertheless, there are still not many learning practices aimed at enhancing computational thinking skills for students. Even in Indonesia, the study of Computitatioan thinking is still very minimal. Using a library review, this article will discuss the computational thinking skills in problem-solving and examples of implementation in school learning.